2021
DOI: 10.3389/fcimb.2021.672527
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of CD4+ T Cell Function as a Strategy for Improving Antibiotic Therapy Efficacy in Tuberculosis: Does It Work?

Abstract: Tuberculosis (TB), caused by Mycobacterium tuberculosis (Mtb) remains a major public health problem worldwide due in part to the lack of an effective vaccine and to the lengthy course of antibiotic treatment required for successful cure. Combined immuno/chemotherapeutic intervention represents a major strategy for developing more effective therapies against this important pathogen. Because of the major role of CD4+ T cells in containing Mtb infection, augmentation of bacterial specific CD4+ T cell responses ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…One possible hypothesis is the reduction of ESAT6/CFP10 expression by bacteria in response to chemotherapy-induced stress. Studies have shown that direct injection of Th1-polarized ESAT-6-specific CD4 + T cell clones cannot reduce bacterial loads in chemotherapeutic Mtb -infected mice [ 38 ]. The level of MHC-II associated ESAT-6 peptide on the surface of infected cells is reduced, thereby limiting the response of these lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…One possible hypothesis is the reduction of ESAT6/CFP10 expression by bacteria in response to chemotherapy-induced stress. Studies have shown that direct injection of Th1-polarized ESAT-6-specific CD4 + T cell clones cannot reduce bacterial loads in chemotherapeutic Mtb -infected mice [ 38 ]. The level of MHC-II associated ESAT-6 peptide on the surface of infected cells is reduced, thereby limiting the response of these lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Given that similar results were observed in our study, approaches to boosting Th1/Th17 responses during the initial phase of antibiotic treatment against antigens that are highly expressed in actively dividing bacteria can feasibly be reconsidered. This may be attributed to the fact that the antibiotic-derived elimination of replicating bacteria might precede the targeting of Th1/Th17 responses [ 81 ]. In fact, paradoxical responses (PRs) can occasionally develop during mycobacterial infection, leading to acute inflammation and increased bacterial burden and thus to a need for further surgical treatment [ 82–86 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Costa et al . demonstrated that enhanced antibiotic clearance of Mtb was not achieved via either the adoptive transfer of ESAT-6- or Ag85B-specific Th1-polarized CD4 + T cells (C7 and P25 cells, respectively) or the intravenous injection of the ESAT-6 1-20 or Ag85B 280-294 peptide during the initial month of chemotherapy for the purpose of boosting Th1 responses [ 81 ]. Given that similar results were observed in our study, approaches to boosting Th1/Th17 responses during the initial phase of antibiotic treatment against antigens that are highly expressed in actively dividing bacteria can feasibly be reconsidered.…”
Section: Discussionmentioning
confidence: 99%